A Comparison of Formation Methods for Graphite//LiFePO4 Cells. Issue 3 (18th January 2019) - Moretti, Arianna; Sharova, Varvara; Carvalho, Diogo V.; Boulineau, Adrien; Porcher, Willy; de Meatza, Iratxe; Passerini, Stefano
Abstract: The sequence of initial cycles necessary for the build‐up of the solid electrolyte interphase (SEI) on the anode surface of Li‐ion batteries (usually called formation) is a cost‐ and time‐consuming process, thus requiring further optimization. Herein, three different protocols are compared to explore possibilities to reduce the formation time of the cells without negatively affecting the electrochemical performance. XPS and HRTEM analyses are used to identify the main characteristics of the as formed SEIs. Electrochemical tests are conducted on full lithium‐ion cells using state‐of‐the‐art graphite and LiFePO4 electrodes. The time‐saving dual‐current protocol results in excellent cycling performance, and in a LiF‐rich SEI. Interestingly, the use of moderately high temperature (40 °C) does not strongly affect the SEI composition as evidenced by XPS analysis. On the other hand, the formation rate determines the degree of graphite surface amorphization, visualized by HRTEM. Abstract : Time is money ! The formation step is a bottleneck in the Li‐ion cell production process. Here, different formation protocols for graphite//LiFePO4 cells are compared aiming to reduce the formation time while maintaining cycle life. High‐resolution transmission electron microscopy (HRTEM) and X‐rays photoemission spectroscopy (XPS) are employed to analyse the formed solid electrolyte interphase (SEI).